Political Secularism and Religion (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint delves into the relationship between religious leaders and movements and secular political systems. While the secularisation thesis predicted the decline of religion in both private and public life, this reprint challenges this narrative by exploring the diverse approaches of religious actors towards politics within secular systems. The reprint includes theoretical explorations and country case studies, analyzing the roles of religious leaders in the political arena of secular countries. From radical movements seeking to establish a religious state to those embracing participation in electoral processes, the authors examine the practical and prescriptive dimensions of religion's engagement with politics. With its interdisciplinary approach and timely subject matter, this book is essential reading for anyone interested in the complex and dynamic relationship between religion and politics in the modern world.